Can the progression of myopia be restrained by monolateral excimer laser correction? - A. T. Khandzhyan; E. P. Tarutta; N. V. Khodzhabekyan; M. A. Khrabrova (Российский офтальмологический журнал, 2020)
The purpose of this study was a comparative assessment of the refraction and the axial length (AL)  changes occurring in the operated and unoperated  eyes of patients with anisometropic  myopia who underwent  unilateral  excimer laser correction.Material  and methods. We observed 13 patients (8 women and 5 men) aged 21 to 53 years (34.2 ± 8.6) with anisometropic myopia (averagely, with spherical equivalent of refraction -3.87 ± 1.77 D in one eye and 0.71 ± 0.71 D in the other), who underwent unilateral LASIK. The observation period was 3-5 years (averagely 3.5 ± 1.1 years). The observation included autorefractometry on a Nidek ARK-530A apparatus, ultrasound biometry on a Nidek US-1800 Echosсan (Japan), and pachymetry on a GALILEI G6 (Ziemer, Switzerland).Results. No significant changes in refraction or axial length were observed either in operated or fellow eyes. Changes in the axial length were controversial: 7 operated and 7 fellow eyes showed an increasing tendency while another 6 operated and 6 fellow eyes showed a decreasing tendency (p > 0.05).Conclusion. The data obtained fail to support the assumption that excimer laser reshaping of the cornea produces an inhibitory effect on the development of myopia.